1956
DOI: 10.1113/jphysiol.1956.sp005630
|View full text |Cite
|
Sign up to set email alerts
|

Some effects of adrenaline, noradrenaline and acetylcholine on the foetal circulation in the lamb

Abstract: In the mature foetal lamb most of the blood which reaches the coronary arteries comes from the inferior vena cava through the foramen ovale. A substance injected into a femoral vein will be carried up into the inferior vena cava, and be diluted with a large quantity of blood returning from the placenta; about two-thirds will pass to the left atrium, and one-third to the right atrium (Dawes, Mott & Widdicombe, 1954). The two-thirds which passes into the left atrium will be still further diluted with blood retur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

1961
1961
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(27 citation statements)
references
References 12 publications
1
26
0
Order By: Relevance
“…Barcroft and Barron (1) detected acute bradycardia in response to injection of epinephrine or norepinephrine and found that it was abolished by vagal section. This was confirmed by Dawes et al (2) in fetuses as young as 90 days. In animals near term, acute carotid occlusion causes a rise of arterial pressure, and impulses with the same periodicity as the heart rate can be detected in the afferent nerve from the carotid sinus (4, 11).…”
Section: Figuresupporting
confidence: 66%
See 1 more Smart Citation
“…Barcroft and Barron (1) detected acute bradycardia in response to injection of epinephrine or norepinephrine and found that it was abolished by vagal section. This was confirmed by Dawes et al (2) in fetuses as young as 90 days. In animals near term, acute carotid occlusion causes a rise of arterial pressure, and impulses with the same periodicity as the heart rate can be detected in the afferent nerve from the carotid sinus (4, 11).…”
Section: Figuresupporting
confidence: 66%
“…Although other workers have shown that baroreflex responses could be elicited in fetal (1)(2)(3)(4) and newborn (1) animals, all previous studies have been conducted in anesthetized animals with the fetus exteriorized. Since it is now well known that cardiovascular function in the fetus may be altered by anesthesia or exterioration (5), we studied fetal lambs in utero while the unsedated ewe stood quietly.…”
mentioning
confidence: 99%
“…It is well established in the fetal lamb that the heart slows when the arterial pressure is raised (Barcroft & Barron, 1945;Dawes, Mott & Rennick, 1956;Biscoe, Purves & Sampson, 1969;Brinkman, Ladner, WVeston & Assali, 1969). This has been confirmed in recent studies with unanaesthetized fetal lambs in utero, and the fall of heart rate has been attributed to baroreflex mechanisms (Shinebourne, Vapaavouri, Williams, Heymann & Rudolph, 1972;Maloney, Cannata, Dowling, Else & Ritchie, 1977;Ismay, Lumbers & Stevens, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…Injection of the same doses of cyanide into a jugular vein, the right ventricle, pulmonary or common carotid arteries of foetal lambs caused INTRODUCTION It was concluded from previous observations that the foetal circulation might well be under effective reflex control by systemic arterial chemoreceptors (Campbell, Dawes, Fishman & Hyman, 1967 a). Since cervical vagotomy caused a fall in arterial pressure near term (Reynolds, 1954;Dawes, Mott & Rennick, 1956;Born, Dawes & Mott, 1956), and the observations of Snyder & Rosenfeld (1937), Barcroft & Karvonen (1948) and Purves & Biscoe (1966) suggested that the carotid chemoreceptors were relatively inactive, it seemed possible that the aortic chemoreceptors might be involved.…”
mentioning
confidence: 99%